Mapping of Deep Tectonic Structures of Central and Southern Cameroon by an Interpretation of Surface and Satellite Magnetic Data - Constantin Mathieu Som Mbang; Charles Antoine Basseka; Joseph Kamguia; Jacques Etamè; Cyrille Donald Njiteu Tchoukeu; Marcelin Pemi Mouzong (International Journal of Geophysics)
The aim of this study is to determine the depth of deep tectonic structures observed in the Adamawa-Yadé zone (central part of Cameroon) and propose a new structural map of this area. The horizontal gradient associated with upward continuation and the 3D Euler deconvolution methods have been applied to the Earth Magnetic Anomaly Grid 2 (EMAG2) data from the study area. The determination of the maximum magnitude of the horizontal gradient of the total magnetic intensity field reduced to the equator, in addition to the main contacts deducted by Euler solution, allowed the production of a structural map to show the fault systems for the survey area. This result reveals the existence of two structural domains which is thus confirmed by the contrast of magnetic susceptibility in the Central Cameroon Zone. The suggested depths are in the range of 3.34 km to 4.63 km. The structural map shows two types of faults (minors and majors) with W-E, N-S, NW-SE, NE-SW, ENE-WSW, WNW-ESE, NNE-SSW, and NNW-SSE trending. The major faults which are deepest (3.81 km to 4.63 km) with NE-SW, W-E, and N-S direction are very represented in the second domain which includes the Pangar-Djerem zone. This domain which recovers many localities (Ngaoundéré, Tibati, Ngaoundal, Yoko Bétaré-Oya, and Yaoundé) is associated with the Pan-African orogeny and the Cameroon Volcanic Line.